CCNA self-study : CCNNA ICND exam certification guide - ODOM, Wendell (Indianapolis : Cisco Press, 2004)
CCNA ICND Exam Certification Guide is a best-of-breed Cisco® exam study guide that has been completely updated to focus specifically on the objectives for the CCNA ICND exam. The official self-study test preparation guide for the Cisco CCNA ICND exam 640-811.
Includes index
Keywords: Electronic data processing personnel Certification, Computer networks Examinations , Internetworking (Telecommunication) , Local area networks (Computer networks), Cisco Systems, Inc , Computer network protocols , Computer networks Design , Routers (Computer networks)